2019
DOI: 10.1080/13814788.2019.1639667
|View full text |Cite
|
Sign up to set email alerts
|

Right bundle branch block: Prevalence, incidence, and cardiovascular morbidity and mortality in the general population

Abstract: Background: Right bundle branch block (RBBB) is among the most common electrocardiographic abnormalities. Objectives: To establish the prevalence and incidence of RBBB in the general population without cardiovascular events (CVE) and whether RBBB increases cardiovascular morbidity and mortality compared with patients with a normal electrocardiogram (ECG). Methods: A historical study of two cohorts including 2981 patients from 29 primary health centres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
3
14
2
1
Order By: Relevance
“…Figure 5 C shows the model's identification of deep S waves in lead V1 for LBBB. Typically, RBBB is detected with an RSR′ QRS complex in lead V1 as shown in Figure 5 E. Observations from Figures 5 C and 5E are compatible with the corresponding diagnostic criteria for LBBB and RBBB ( Alventosa-Zaidin et al., 2019 ; Goldberger et al., 2017 ). More interpretation results can be found in Figure S3 .…”
Section: Resultssupporting
confidence: 69%
“…Figure 5 C shows the model's identification of deep S waves in lead V1 for LBBB. Typically, RBBB is detected with an RSR′ QRS complex in lead V1 as shown in Figure 5 E. Observations from Figures 5 C and 5E are compatible with the corresponding diagnostic criteria for LBBB and RBBB ( Alventosa-Zaidin et al., 2019 ; Goldberger et al., 2017 ). More interpretation results can be found in Figure S3 .…”
Section: Resultssupporting
confidence: 69%
“… 25 Around 5% of the patients in our study had right and left bundle branch blocks, which is like a previous study. 26 The prevalence of the left bundle branch block was higher in the previous study, and this difference is likely due to the lower percentage of the heart failure patients in our study. 27 …”
Section: Discussioncontrasting
confidence: 50%
“…4 Incomplete RBBB was not reported in our registry; a recent study among general population in Spain showed no effect of incomplete RBBB on morbidity and mortality. 18 Xiong et al evaluated 19 cohort studies (201 437 participants) in a meta-analysis and found that RBBB was associated with an increased risk of mortality in a general population as well as patients with heart disease. 1 A significantly higher risk of in-hospital mortality (risk ratio [RR]: 2.31), 30-day mortality (RR: 2.85), and long-term mortality (RR: 1.96) was associated with RBBB.…”
Section: Discussionmentioning
confidence: 99%
“…4 Incomplete RBBB was not reported in our registry; a recent study among general population in Spain showed no effect of incomplete RBBB on morbidity and mortality. 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation